PENGARUH SIFAT MACHIAVELLIAN, KARAKTER PERSONAL, DAN KINERJA PEGAWAI TERHADAP PERILAKU DISFUNGSIONAL AUDITOR (Studi Empiris pada Perwakilan Inspektorat di Provinsi Banten) - Laras Setiyani; Ilham Maulana Saud (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2018)
This study aims to analyze the effect of Machievellian traits, personal character, and employee performance on the dysfunctional behavior of auditors at the Inspectorate Representative in Banten Region. Subjects in this study were internal auditors who worked in the inspectorate with supervisory and auditor positions taken 3 places, namely: the city of Tangerang, the city of South Tangerang and the district of Tangerang. The sample amounted to 103 respondents using convenience sampling method. The analytical tool used is SPSS. Based on the analysis that has been carried out, the results showed that: (1) the effect of Machievellian traits was not found to significantly influence the dysfunctional behavior of auditors, (2) the effect of internal locus of control significantly affected the dysfunctional behavior of auditors, (3) the effect of turnover intention significantly affected dysfunctional behavior of auditors, (4) the effect of employee performance has a significant effect on auditor dysfunctional behavior.